Historical Analysis Of Akbar Period Architecture - Rahimov Laziz Abduazizovich PhD (Genius Journals, 2023)
In given article we will try to analyze architecture of Akbar period and it`s evolution process. Moreover, we will try to clear up the role of Akbar in formation of Baburid architecture. Lastly, we describe how Akbar`s buildings has begun and its development over the years, also, we have given an evidence supporting our points.
Keywords: Akbar`s architecture; Central Asian architecture; architecture of Delhi and Fathpur Sikri.